Community Education on Upper Respiratory Tract Infections and Peppermint Oil Inhalation Therapy - Desreza, Nanda; Nafis, Badratun (Transpublika Publisher, 2025)
Upper respiratory tract infections (URTIs) is a condition in which a person suddenly expels air from the thoracic cavity through the epiglottis and mouth, usually accompanied by a cough with phlegm or no phlegm. Coughs and colds are common complaints experienced by children and adults, generally caused by viral infections such as influenza. The disease can affect the upper respiratory tract, including the lungs, nose and throat. Traditional treatments such as simple inhalation using peppermint oil can help alleviate URTI symptoms. This study aims to improve the community's understanding of the identification and traditional treatment of Acute Respiratory Infections (ARI), as well as assess the role of nurses in providing nursing care through simple inhalation therapy. In this activity, the nurse acts as a care giver who provides comprehensive nursing care, starting from assessment to evaluation. Based on the results of community service activities in Fampong Lam Neuheun, Kuta Baro, Aceh Besar, it is known that the community has gained a better understanding in recognizing the symptoms of URTI and performing traditional medicine appropriately.